2005
DOI: 10.1158/0008-5472.can-04-3567
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Cell Hyperplasia and Carcinomas in Urinary Bladders of Transgenic Mice with Keratin 5 Promoter-Driven Cyclooxygenase-2 Overexpression

Abstract: The inducible form of cyclooxygenase (COX), COX-2, is upregulated in many epithelial cancers and its prostaglandin products increase proliferation, enhance angiogenesis, and inhibit apoptosis in several tissues. Pharmacologic inhibition and genetic deletion studies showed a marked reduction of tumor development in colon and skin. COX-2 has also been strongly implicated in urinary bladder cancer primarily by studies with nonselective COX-and COX-2-selective inhibitors. We now show that forced expression of COX-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 36 publications
1
43
0
1
Order By: Relevance
“…However, inconsistent results were obtained in another recent study, which indicates that COX-2 may be sufficient to cause inflammation and the subsequent cancerous aberrations. Within this study, it was found that the forced expression of COX-2 transgene under the control of a keratin-5 promoter causes spontaneous inflammation-associated transitional cell hyperplasia and transitional cell carcinoma in urinary bladders of transgenic mice (186). Future research is needed to address the specific role of COX-2 in linking inflammation and cancer and to extend those findings to other types of inflammationassociated cancers.…”
Section: Key Molecular Players In Linking Inflammation To Cancermentioning
confidence: 84%
“…However, inconsistent results were obtained in another recent study, which indicates that COX-2 may be sufficient to cause inflammation and the subsequent cancerous aberrations. Within this study, it was found that the forced expression of COX-2 transgene under the control of a keratin-5 promoter causes spontaneous inflammation-associated transitional cell hyperplasia and transitional cell carcinoma in urinary bladders of transgenic mice (186). Future research is needed to address the specific role of COX-2 in linking inflammation and cancer and to extend those findings to other types of inflammationassociated cancers.…”
Section: Key Molecular Players In Linking Inflammation To Cancermentioning
confidence: 84%
“…28 When aberrantly expressed in basal epithelial cells of urinary bladder, COX-2 has been shown to induce transitional cell hyperplasia, dysplasia and transitional cell carcinomas. 29 In another model of mammary carcinogenesis, overexpression of COX-2 in mammary glands under the control of the murine mammary tumor virus promoter was sufficient to generate mammary gland hyperplasia, dysplasia and the formation of metastatic cancer in multiparous mice. 30 These studies provided strong evidence for cause-and-effect relationships between COX-2 and the induction of premalignant alterations in diverse epithelia which occasionally develop into overt malignancy.…”
Section: Cyclooxygenase-and Lipoxygenase-catalyzed Arachidonic Acid Mmentioning
confidence: 99%
“…This is associated with the production of angiogenic factors such as vascular endothelial growth factor (VEGF) and/or basic fibroblast growth factor (bFGF). 29,93 The proangiogenic effects of aberrant COX-2 expression are mediated by 4 prostanoids, TXA 2 , PGI 2 , PGF 2a and, in particular, PGE 2 . The latter was shown to reverse the antiangiogenic effects of COX inhibitors.…”
Section: Modulation Of Angiogenesismentioning
confidence: 99%
“…Cystic duct dilatations and proliferative epithelial lesions that showed analogies with the human breast with fi brocystic changes were found in a COX-2-and PG-dependent manner in mammary gland epithelium [26] . In the urinary bladder, the transgene caused transitional cell hyperplasia and spontaneous transitional cell carcinomas [27] . In the cognate human diseases, COX-2 was consistently found to be overexpressed in a high percentage of tested biopsies.…”
Section: Cause-and-effect Relationship Between Aberrant Cox-2 Expressmentioning
confidence: 99%